…The Unthinkable House - Ben Nicholson (Oz, 1993)
Thinking the Unthinkable The idea of a franchise is an intriguing one because its life rotates about a name. Wherever the name goes an entourage of buildings, desks, stoves, storage bins, and countertops follow - to help make the name substantial. Ed. note: See related article, "The Grit and Grist of Thinking...".